Characteristics of Body Composition in a Group of Local South Darfur Male Goats 2: Non-Carcass Characteristics (Journal of Veterinary Medicine and Animal Production, 2021)
Two groups of local intact black and intact white male goats were included in this study. The two goat groups did not perform exclusively to indicate genetic differences in their non-carcass parameters, but feed intake was significantly greater in the older goats (54.5 vs. 51.5 Kg). The heavier SW and HCW were associated with significantly increased feed intake and gastrointestinal tract contents weights but there was a significantly reduced percent empty gastrointestinal tract in association with the heavier HCW only. Also the percent values for the rumen relative to the gastrointestinal tract were significantly (P